Human Development and the Pursuit of the Common Good: Social Psychology or Aristotelian Virtue Ethics? - Martin, Felix (Journal of business ethics, 2011)
The encyclical proclaims the centrality of human development, which includes acting with gratuitousness and solidarity in pursuing the common good. This paper considers first whether such relationships of gratuitousness and solidarity can be analysed through the prism of traditional theories of social psychology, which are highly influential in current management research, and concludes that certain aspects of those theories may offer useful tools for analysis at the practical level. This is contrasted with the analysis of such relationships through Aristotelian virtue ethics (in particular as interpreted by MacIntyre 1985, 1998, 1999), which is emerging as a strong force in the field of business ethics, and which has strong conceptual similarities with the ideas put forward by Benedict XVI. Aristotelian virtue ethics offers a better fit with the aims of the encyclical at the theoretical level but it presents a number of challenges at the practical level, which the paper suggests may be addressed through the integration in its analysis of human action of models derived from social psychology.